The Effect of Baby Massage on The Sleep Duration of Infants Aged 6-12 Months - Rosita Agustina; Shinta Novelia; Rini Kundaryanti (Nursing and Health Sciences Journal (NHSJ), 2022)
Infancy is a golden period in infant growth and development so it needs special attention. One of the factors that can affect a baby's growth and development is sleep and rest. Massage can help reduce muscle tension, so that the benefits obtained by the baby become more relaxed and sleep more soundly. Based on a preliminary study at the Karangpawitan Health Center, it was found that the number of babies who had sleep disorders was 11 babies or about 42.3% of 26 babies. The results of interviews with 10 mothers of babies, 7 people (70%) did not know about baby massage. The purpose of this study was to determine the effect of baby massage on the sleep duration of infants aged 6-12 months at Posyandu Cempaka, Karangsari Village, Karangpawitan District, Garut Regency. This study uses a quasi-experimental study with the one group pretest-posttest design. The population in this study was 35 infants aged 6-12 months, the sample technique used was total sampling, 5 respondents were eliminated so that the sample taken was 30 infants. The instrument used was a questionnaire that has been tested for validity and reliability. Data were analyzed by using Paired Samples Test. The average duration of sleep for babies before being given baby massage was 12,933 and the average duration of sleep for babies after being given baby massage was 14,200. The results of the statistical test showed a p-value of 0.000 <0.05. There was an effect of baby massage on the sleep duration of infants aged 6-12 months. It is hoped that mothers can continue to massage their children by learning baby massage so that they can massage themselves at home regularly and routinely so that babies do not experience sleep disturbances and can grow and develop optimally.